Radiation and energy budget dynamics associated with a floating photovoltaic system. (1st November 2021) - Yang, Peipei; Chua, Lloyd H.C.; Irvine, K.N.; Imberger, Jorg
Highlights: Little to no study on impacts of floating photovoltaic panels on reservoir surfaces. An experimental study was conducted to collect field data. A numerical model was developed to model radiation and energy dynamics. Reversals in the major heat flux components observed. Water surface energy balance occurs at a higher equilibrium temperature. Abstract: Shortwave radiation, longwave radiation, photovoltaic (PV) panel, air and near-surface water temperature data were measured for a floating PV system installed in a shallow tropical reservoir. Similar air and water temperature measurements were conducted in open water (ambient condition) for comparison. The data indicate that shortwave radiation is reduced significantly under the PV panels while the longwave radiation increased, and in fact became higher than the shortwave radiation as compared to open water conditions. The air temperature and the water temperature under the PV panels are higher than in open water. A numerical model was developed to predict the PV panel temperature, air and water temperatures beneath the panels and to investigate the heat balance at the reservoir surface, beneath the panels. The modelled air and PV panel temperatures were in good agreement with the field data. The modelled surface water temperature also replicated field measurements showing an increase of about 0.5 °C as compared to the open water temperature. Heat budget analysis showed that the thermal dynamics under the PV panels is mainly controlled by the longwave radiation from the PV panels and reduction in latent heat flux. The altered flux conditions beneath the panels result in a higher equilibrium temperature near the water surface, compared to open water conditions.